Reliability and Validity of a New Diagnostic Device for Quantifying Hemiparetic Arm Impairments: An Exploratory Study - Levinia Lara van der Velden; Joyce Lisanne Benner; Bram Onneweer; Claudia Josephina Wilhelmina Haarman; Ruud Selles; Gerard Ribbers; Marij Eugenie Roebroeck (Medical Journals Sweden, 2022)
Objective: To assess test-retest reliability and validity of a new diagnostic device, the Shoulder Elbow Perturbator, to quantify muscle weakness, abnormal synergy, (muscle activity-related) spasticity, and changes in viscoelastic joint properties of the elbow. Subjects: Stroke patients, adults with cerebral palsy and healthy controls. Methods: Test-retest reliability was evaluated using intra-class correlations (ICC) and assessment of measurement error. The device's validity was evaluated by demonstrating differences between patients and healthy controls, and correlations of spasticity and abnormal synergy outcomes using the clinical Modified Tardieu Scale, the Fugl-Meyer Assessment, and the Test of Arm Selective Control. Results: Reliability was excellent, with an ICC > 0.75 for synergy and ICCs > 0.90 for all other impairments, with relatively small measurement errors. Validity was confirmed by group differences between patients and healthy controls for muscle weakness, spasticity, and viscoelastic joint properties, but not for abnormal synergy. Correlation analysis with clinical scales confirmed validity for spasticity, while, for synergy, correlations were found in the patients with stroke, but not those with cerebral palsy. Conclusion: This new diagnostic device is a reliable and valid instrument to assess multiple upper limb impairments in patients with neurological conditions, supporting its use in clinical practice. Further studies are needed to confirm these findings. LAY ABSTRACT Reliable and valid quantitative measurement of arm impairments due to neurological conditions is important for clinical decision-making. Current clinical measurement tools are subjective and not reliable. The aim of this study was therefore to assess the reliability and validity of a new diagnostic device to quantify multiple arm impairments (muscle weakness, abnormal synergy, spasticity, changes in viscoelastic joint properties) in patients with stroke, adults with cerebral palsy (CP), and healthy controls. Reliability was excellent for all impairments and was analysed by testing the consistency of the results on 2 occasions in the same subject. Validity was confirmed by group differences between patients and healthy controls for all impairments, except for synergy. Also, correlations of the results with clinical measurement tools were found for spasticity and synergy, except for synergy in patients with CP. In conclusion, this new diagnostic device is a reliable and valid instrument to assess multiple impairments of the elbow in patients with neurological conditions. Further studies are needed to confirm these findings.